Razvitie zritel'nogo vospriiatiia v protsesse formirovaniia elementarnykh matematicheskikh predstavlenii u doshkol'nikov s narusheniem zreniia - Proskurina E. N., Bolotskikh N. V., Rudneva S. V., Drovnikova T. A. (Pedagogical experience: from theory to practice, 2022)
For the development of visual perception, activation of visual functions, it is necessary to use all types of children's activities: play, work, classes and everyday activities.
Keywords: коррекция; зрение; слабовидящие; зрительный анализатор; зрительное восприятие; correction; vision; visually impaired; visual analyzer; visual perception